A level set solution to the stress-based structural shape and topology optimization - Xia, Qi; Shi, Tielin; Liu, Shiyuan; Wang, Michael Yu (Computers & structures, 2012)
► We present a level set solution to stress-based shape and topology optimization. ► A novel global measure of stress is proposed. ► Shape sensitivity analysis is performed via the material derivative method. ► Artificial weak material usually used in level set method to mimic void is avoided. ► Peak stress can be effectively controlled. We present a level set solution to the stress-based structural shape and topology optimization. First, a novel global measure of stress is proposed, and the optimization problem is formulated to minimize the global measure of stress subject to a constraint of material volume. In order to solve this optimization problem, the level set method is employed. The finite element analysis is accomplished by modifying a fixed background mesh, and the artificial weak material that is conventionally used in the level set method to mimic void is avoided in the present work.